Kewenangan Kejaksaan dalam Melakukan Penahanan terhadap Pelaku Tindak Pidana Ujaran Kebencian di Sosial Media - Louis Muda Adam Gesi Radja; I Nyoman Gede Sugiartha; Ni Made Sukaryati Karma (Warmadewa Press, 2022)
Authority is what is called formal power, power comes from legislative power (given by law) or from executive administrative power. Authority, which usually consists of several powers, is power over a certain group of people or power over an area of ​​government. The purpose of this study is to analyze the arrangement of the prosecutor's authority in detaining the perpetrators of hate speech crimes on social media and to discuss the prosecutor's obstacles in detaining the perpetrators of hate speech acts carried out on social media. This research was conducted using a normative research type. The method used is normative legal research. This research approach is a conceptual and literature approach, with the primary legal sources coming from legislation and decisions, while the secondary legal sources come from legal journals and law books. The technique of collecting legal materials for this research, by collecting the literature study. Then it can be obtained that the prosecutor's authority is regulated in the criminal procedural law book, the prosecutor's authority law, which includes several laws, including Law no. it can be ascertained about the rights and authorities of the prosecutor so that law enforcers, especially the prosecutor's office, can make detentions in accordance with the rules that have been in force, so that there is no abuse of authority by law enforcers, especially the prosecutor and as appropriate the prosecutor is obliged to realize equality for all Indonesian citizens who are entangled in cases criminal, civil or otherwise.